Diversity and Activity of Alternative Nitrogenases in Sequenced Genomes and Coastal Environments - McRose, Darcy L.; Zhang, Xinning; Kraepiel, Anne M. L.; Morel, François M. M. (Frontiers in Microbiology, 2017)
The nitrogenase enzyme, which catalyzes the reduction of N2 gas to NH4+, occurs as three separate isoenzymes that use Mo, Fe-only, or V. The majority of global nitrogen fixation is attributed to the more efficient ‘canonical’ Mo-nitrogenase, whereas Fe-only and V-(‘alternative’) nitrogenases are often considered ‘backup’ enzymes, used when Mo is limiting. Yet, the environmental distribution and diversity of alternative nitrogenases remains largely unknown. We searched for alternative nitrogenase genes in sequenced genomes and used PacBio sequencing to explore the diversity of canonical (nifD) and alternative (anfD and vnfD) nitrogenase amplicons in two coastal environments: the Florida Everglades and Sippewissett Marsh (MA). Genome-based searches identified an additional 25 species and 10 genera not previously known to encode alternative nitrogenases. Alternative nitrogenase amplicons were found in both Sippewissett Marsh and the Florida Everglades and their activity was further confirmed using newly developed isotopic techniques. Conserved amino acid sequences corresponding to cofactor ligands were also analyzed in anfD and vnfD amplicons, offering insight into environmental variants of these motifs. This study increases the number of available anfD and vnfD sequences 20-fold and allows for the first comparisons of environmental Mo-, Fe-only, and V-nitrogenase diversity. Our results suggest that alternative nitrogenases are maintained across a range of organisms and environments and that they can make important contributions to nitrogenase diversity and nitrogen fixation.